course Mth 158
......!!!!!!!!...................................
10:44:08 query R.2.46 (was R.2.36) Evaluate for x = -2, and y = 3 the expression (2x - 3) / y and explan how you got your result.
......!!!!!!!!...................................
RESPONSE --> (2(-2) - 3) / 3 = ((-4) - 3) / 3 = -7 / 3 First I replaced the x and y values with the appropriate numbers. Then I multiplied (2(-2)) to get (-4). Then I subtracted 3 from -4 to get -7. The most reduced fraction possible is (-7 / 3).
.................................................
......!!!!!!!!...................................
10:44:20 ** Starting with (2x-3)/y we substitute x=-2 and y=3 to get (2*(-2) - 3)/3 = (-4-3)/3= -7/3. **
......!!!!!!!!...................................
RESPONSE --> Ok.
.................................................
......!!!!!!!!...................................
10:49:44 query R.2. 55 (was R.2.45) Evaluate for x = 3 and y = -2: | |4x| - |5y| | and explan how you got your result.
......!!!!!!!!...................................
RESPONSE --> | |4(3)| - |5(-2)| | = | |12| - |10| | = |2| = 2 I substituted the x and y values with the appropriate number. I then multiplied (4(3)) and (5(-2)), to get (12) and (10). The absolute symbols invalidate the negative of (-2), thus (10) is positive. Then I subtracted (10) from (12) to get 2.
.................................................
......!!!!!!!!...................................
10:50:38 query R.2.64 (was R.2.54) Explain what values, if any, must not be present in the domain of the expression (-9x^2 - x + 1) / (x^3 + x)
......!!!!!!!!...................................
RESPONSE --> Ok.
.................................................
Ӏj|btz_L{ assignment #002 fzۣO College Algebra 06-01-2006
......!!!!!!!!...................................
10:54:42 query R.2.46 (was R.2.36) Evaluate for x = -2, and y = 3 the expression (2x - 3) / y and explan how you got your result.
......!!!!!!!!...................................
RESPONSE --> (2(-2) - 3) / 3 = (-4 - 3) / 3 = -7 / 3 I subsituted the appropriate values for x and y. Then I multiplied (2(-2) to get (-4), after which I subtracted (3) from it. This gave me (-7), and as (-7) cannot be divided by (3) into a integer, I left it as a fraction.
.................................................
......!!!!!!!!...................................
10:54:48 ** Starting with (2x-3)/y we substitute x=-2 and y=3 to get (2*(-2) - 3)/3 = (-4-3)/3= -7/3. **
......!!!!!!!!...................................
RESPONSE --> Ok.
.................................................
......!!!!!!!!...................................
10:57:24 query R.2. 55 (was R.2.45) Evaluate for x = 3 and y = -2: | |4x| - |5y| | and explan how you got your result.
......!!!!!!!!...................................
RESPONSE --> | |4(3)| - |5(-2)| | = | |12| - |10| | = |2| = 2 I substituted the appropriate values for x and y. Then i multiplied (4 * 3) to get (12) and (5 * 2) to get (10). The absolute symbols invalidate the negative in (-2), so it becomes (2), making (10) positive. Then I subtracted (10) from (12) to get (2).
.................................................
......!!!!!!!!...................................
10:57:42 ** Starting with | | 4x |- | 5y | | we substitute x=3 and y=-2 to get | | 4*3 | - | 5*-2 | | = | | 12 | - | -10 | | = | 12-10 | = | 2 | = 2. **
......!!!!!!!!...................................
RESPONSE --> Ok, no need to write so much, apparently.
.................................................
......!!!!!!!!...................................
11:01:20 query R.2.64 (was R.2.54) Explain what values, if any, must not be present in the domain of the expression (-9x^2 - x + 1) / (x^3 + x)
......!!!!!!!!...................................
RESPONSE --> {x | x is not equal to 0 or -1} A zero will make the denominator equal to zero (0^3 + 0 = 0), and that makes the fraction undefined. A (-1) has the same effect ((-1)^3 + -1) = 0).
.................................................
......!!!!!!!!...................................
11:04:01 ** The denominator of this expression cannot be zero, since division by zero is undefined. Since x^3 + x factors into (x^2 + 1) ( x ) we see that x^3 + x = 0 only if x^2 + 1 = 0 or x = 0. Since x^2 cannot be negative x^2 + 1 cannot be 0, so x = 0 is indeed the only value for which x^3 + x = 0. **
......!!!!!!!!...................................
RESPONSE --> Ok, so [(-1)^2 + 1) = 2], then (2 + (-1) = 1), therefore (-1) can be in the domain. I didn't realize it could be factored
.................................................
......!!!!!!!!...................................
11:08:10 query R.2.73 (was R.4.6). What is (-4)^-2 and how did you use the laws of exponents to get your result?
......!!!!!!!!...................................
RESPONSE --> The law of [(a^m)^n = a^mn] can be used to answer this question. (-4) is raised to the first power, and that product is raised by the 2cd power. (-4) * (-4) = 16.
.................................................
......!!!!!!!!...................................
11:09:50 **Since a^-b = 1 / (a^b), we have (-4)^-2 = 1 / (-4)^2 = 1 / 16. **
......!!!!!!!!...................................
RESPONSE --> The problem in the book is written as (-4)^2, unlike the program, which has it as (-4)^-2, which gives a different answer.
.................................................
......!!!!!!!!...................................
11:19:24 query Extra Problem. What is (3^-2 * 5^3) / (3^2 * 5) and how did you use the laws of exponents to get your result?
......!!!!!!!!...................................
RESPONSE --> (3^-2 * 5^3) / (3^2 * 5) = [(1 / 3^2) * 5^3] / (3^2 * 5) = [(1 / 9) * 125] / (9 * 5) = [(125 / 9)] / (45) = 25 / 81 The first law used was [(a^-n) = (1 / a^n) if a is not 0]. This changed (3^-2) to (1 / 3^2). Then I evaluated all the exponents, so : (1 / 3^2) became (1 / 9), (5^3) became (125), (3^2) became (9). Then I followed the rest of the order of operations to arrive at (25 / 81).
.................................................
......!!!!!!!!...................................
11:22:15 ** (3^(-2)*5^3)/(3^2*5). Grouping factors with like bases we have 3^(-2)/3^2 * 5^3 / 5. Using the fact that a^b / a^c = a^(b-c) we get 3^(-2 -2) * 5^(3-1), which gives us 3^-4 * 5^2. Using a^(-b) = 1 / a^b we get (1/3^4) * 5^2. Simplifying we have (1/81) * 25 = 25/81. **
......!!!!!!!!...................................
RESPONSE --> That's a different way of doing what I did. In this method, you group the (3) and the (5) bases. The second law used, [a^b / a^c = a^(b-c)], was not in the book, but perhaps it was in the CD. I'll have to look that over when I get home. We still get the same answer, but my guess is that this is the proper way to do it.
.................................................
......!!!!!!!!...................................
11:36:38 query R.2.94. Express [ 5 x^-2 / (6 y^-2) ] ^ -3 with only positive exponents and explain how you used the laws of exponents to get your result.
......!!!!!!!!...................................
RESPONSE --> most likely wrong, but . . . [(5x^-2) / (6y^-2]^-3 = [(1 / 5x^2) / (1 / 6y^2)]^-3 =
.................................................
......!!!!!!!!...................................
11:39:25 [ 5 x^-2 / (6 y^-2) ] ^ -3 = (5 x^-2)^-3 / (6 y^-2)^-3, since (a/b)^c = a^c / b^c. This simplifies to 5^-3 (x^-2)^-3 / [ 6^-3 (y^-2)^-3 ] since (ab)^c = a^c b^c. Then since (a^b)^c = a^(bc) we have 5^-3 x^6 / [ 6^-3 y^6 ] . We rearrange this to get the result 6^3 x^6 / (5^3 y^6), since a^-b = 1 / a^b.
......!!!!!!!!...................................
RESPONSE --> Yeah, I was wrong, and I don't understand any of the answer. Apparently, I used the right laws (or two of the right laws), just in the wrong order, and I will need help with this.
.................................................
......!!!!!!!!...................................
11:45:00 query Extra Problem. Express (-8 x^3) ^ -2 with only positive exponents and explain how you used the laws of exponents to get your result.
......!!!!!!!!...................................
RESPONSE --> (-8x^3)^-2 = (-8^-2)(x^3)^-2 = (-8^-2)(x^-6) = (1 / (-8^2)x^6) = (1 / 64x^6) first law: [(ab)^n = a^n b^n] second law: [(a^m)^n = a^mn] third law: [a^-n = (1 / a^n)]
.................................................
......!!!!!!!!...................................
11:48:59 ** ERRONEOUS STUDENT SOLUTION: (-8x^3)^-2 -1/(-8^2 * x^3+2) 1/64x^5 INSTRUCTOR COMMENT:1/64x^5 means 1 / 64 * x^5 = x^5 / 64. This is not what you meant but it is the only correct interpretation of what you wrote. Also it's not x^3 * x^2, which would be x^5, but (x^3)^2. There are several ways to get the solution. Two ways are shown below. They make more sense if you write them out in standard notation. ONE CORRECT SOLUTION: (-8x^3)^-2 = (-8)^-2*(x^3)^-2 = 1 / (-8)^2 * 1 / (x^3)^2 = 1/64 * 1/x^6 = 1 / (64 x^5). Alternatively (-8 x^3)^-2 = 1 / [ (-8 x^3)^2] = 1 / [ (-8)^2 (x^3)^2 ] = 1 / ( 64 x^6 ). **
......!!!!!!!!...................................
RESPONSE --> I must remember to put parenthesis around figures that need to be treated as a single term. I see where I made a mistake using the alternative solution, the closest to mine. I should have used the law of (a^-n) = (1 / a^n) first, and then do everything else, instead of using it last in this case. It's looking more and more like I need help with exponents.
.................................................
......!!!!!!!!...................................
11:58:05 query R.2.90 (was R.4.36). Express (x^-2 y) / (x y^2) with only positive exponents and explain how you used the laws of exponents to get your result.
......!!!!!!!!...................................
RESPONSE --> (x^-2 y) / (x y^2) = [(x^-2) / (x)] * [(y) / (y^2)] = (x / x^2) * (y / y^2) =
.................................................
......!!!!!!!!...................................
11:59:11 ** (1/x^2 * y) / (x * y^2) = (1/x^2 * y) * 1 / (x * y^2) = y * 1 / ( x^2 * x * y^2) = y / (x^3 y^2) = 1 / (x^3 y). Alternatively, or as a check, you could use exponents on term as follows: (x^-2y)/(xy^2) = x^-2 * y * x^-1 * y^-2 = x^(-2 - 1) * y^(1 - 2) = x^-3 y^-1 = 1 / (x^3 y).**
......!!!!!!!!...................................
RESPONSE --> I don't understand, I just don't understand.
.................................................
......!!!!!!!!...................................
12:01:41 query Extra Problem. . Express 4 x^-2 (y z)^-1 / [ (-5)^2 x^4 y^2 z^-5 ] with only positive exponents and explain how you used the laws of exponents to get your result.
......!!!!!!!!...................................
RESPONSE --> I don't know. I've never been that great with exponents, and this program doesn't make it an easier to understand them or what the problem is.
.................................................
......!!!!!!!!...................................
12:02:13 ** Starting with 4x^-2(yz)^-1/ [ (-5)^2 x^4 y^2 z^-5] Squaring the -5 and using the fact that (yz)^-1 = y^1 * z^-1: 4x^-2 * y^-1 * z^-1/ [25 * x^4 * y^2 * z^-5} Grouping the numbers, and the x, the y and the z expression: (4/25) * (x^-2/x^4) * (y^-1/y^2) * (z^-1/z^-5) Simplifying by the laws of exponents: (4/25) * x^(-2-4) * y^(-1-2) * z^(-1+5) Simplifying further: (4/25) * x^-6 * y^-3 * z^4 Writing with positive exponents: 4z^4/ (25x^6 * y^3 ) **
......!!!!!!!!...................................
RESPONSE --> See previous response, and you'll know what I'll say.
.................................................
......!!!!!!!!...................................
12:02:56 query R.2.122 (was R.4.72). Express 0.00421 in scientific notation.
......!!!!!!!!...................................
RESPONSE --> 4.21 * 10^-3
.................................................
......!!!!!!!!...................................
12:03:04 ** 0.00421 in scientific notation is 4.21*10^-3. This is expressed on many calculators as 4.21 E-4. **
......!!!!!!!!...................................
RESPONSE --> Ok.
.................................................
......!!!!!!!!...................................
12:03:26 query R.2.128 (was R.4.78). Express 9.7 * 10^3 in decimal notation.
......!!!!!!!!...................................
RESPONSE --> 9700.0
.................................................
......!!!!!!!!...................................
12:03:36 ** 9.7*10^3 in decimal notation is 9.7 * 1000 = 9700 **
......!!!!!!!!...................................
RESPONSE --> ok.
.................................................
......!!!!!!!!...................................
12:06:04 query R.2.150 (was R.2.78) If an unhealthy temperature is one for which | T - 98.6 | > 1.5, then how do you show that T = 97 and T = 100 are unhealthy?
......!!!!!!!!...................................
RESPONSE --> |97 - 98.6| > 1.5 = |1.6| > 1.5 = A temperature of 97 is unhealthly because it is more than 1.5 degrees away from the norm. |100 - 98.6| > 1.5 = |1.4| > 1.5 = A temperature of 100 is healthy because it is less than 1.5 degrees away from the norm.
.................................................
......!!!!!!!!...................................
12:06:13 ** You can show that T=97 is unhealthy by substituting 97 for T to get | -1.6| > 1.5, equivalent to the true statement 1.6>1.5. But you can't show that T=100 is unhealthy, when you sustitute for T then it becomes | 100 - 98.6 | > 1.5, or | 1.4 | > 1.5, giving us 1.4>1.5, which is an untrue statement. **
......!!!!!!!!...................................
RESPONSE --> Ok.
.................................................
"